A comprehensive review of Schisandra chinensis lignans: pharmacokinetics, pharmacological mechanisms, and future prospects in disease prevention and treatment - Danushiya Ehambarampillai; Murphy Lam Yim Wan (Chinese Medicine)
Abstract Lignans derived from Schisandra chinensis have attracted significant attention for their diverse pharmacological activities and clinical potential. This review presents a comprehensive analysis of the pharmacological properties of Schisandra chinensis lignans, including their antioxidant, anti-inflammatory, neuroprotective, hepatoprotective, antibacterial/viral, antidiabetic and anticancer effects. Their multifaceted mechanisms of action hold promise for therapeutic areas such as cancer, neurodegenerative diseases and metabolic disorders, aligning with urgent clinical needs. Additionally, this review explores the pharmacokinetics of these bioactive compounds, highlighting challenges in their absorption, distribution, metabolism and excretion, which impact their bioavailability. Recent advancements in drug delivery systems are discussed, highlighting their potential to enhance therapeutic efficacy in clinical settings. Furthermore, the synergistic effects of combining these lignans with other therapeutic agents are considered a strategy to increase their efficacy. Future research is imperative to identify additional active components and elucidate novel mechanisms of action, paving the way for expanded therapeutic applications and unlocking the full clinical potential of Schisandra chinensis in disease prevention and treatment.